2016
DOI: 10.1093/schbul/sbv174
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Functional Whole-Brain Network Architecture in Patients With Schizophrenia: A Meta-analysis

Abstract: Findings from multiple lines of research provide evidence of aberrant functional brain connectivity in schizophrenia. By using graph-analytical measures, recent studies indicate that patients with schizophrenia exhibit changes in the organizational principles of whole-brain networks and that these changes relate to cognitive symptoms. However, there has not been a systematic investigation of functional brain network changes in schizophrenia to test the consistency of these changes across multiple studies. A co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(64 citation statements)
references
References 80 publications
5
59
0
Order By: Relevance
“…There is increasing evidence that the psychiatric disorders and the cognitive deficits of patients with schizophrenia are associated with and may be caused by dysfunction of highly-distributed systems displaying disturbed spatiotemporal activity patterns. Moreover, a recent meta-analysis demonstrated significant changes in whole brain network architecture associated with schizophrenia [18]. This supports the notion of functional interactions between multiple molecular, cellular and system pathways, which contribute to the multiple symptoms and cognitive deficits in schizophrenia [19].…”
Section: Introductionsupporting
confidence: 58%
“…There is increasing evidence that the psychiatric disorders and the cognitive deficits of patients with schizophrenia are associated with and may be caused by dysfunction of highly-distributed systems displaying disturbed spatiotemporal activity patterns. Moreover, a recent meta-analysis demonstrated significant changes in whole brain network architecture associated with schizophrenia [18]. This supports the notion of functional interactions between multiple molecular, cellular and system pathways, which contribute to the multiple symptoms and cognitive deficits in schizophrenia [19].…”
Section: Introductionsupporting
confidence: 58%
“…Previous studies exploring brain network organization in schizophrenia showed alterations of several properties [165][166][167][168][169][170]. In particular, reduced hub connectivity [171] and rich club organization have been reported in schizophrenic patients [172].…”
Section: Synaptic Plasticity Dysfunction May Drive Brain Network Disrmentioning
confidence: 96%
“…Regarding its pathophysiology, different models have been proposed, which suggest that alterations in functional connectivity between different brain regions might underlie the variety of symptoms associated with schizophrenia 4,5 . Indeed, a growing body of empirical studies reported aberrant connectivity pattern in patients with schizophrenia where the integration of information across multiple brain areas is compromised resulting in disrupted brain networks [7][8][9][10][11]24 .…”
Section: Discussionmentioning
confidence: 99%
“…Prominent examples are the cognitive dysmetria and disconnection hypothesis [4][5][6]. Indeed, within the last years a growing body of neuroimaging studies report aberrant brain circuitry causing a failure in coordinating information across multiple brain sites [7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%